(3GdefJNH aj JYHjQ GdQDjGs - (3GdMSjf Hf GdMSf Hf EHQGgje GdQGRj, CHh Ydjs
(3ChdgG (B:s
(3CeG HYO (B: (3aGf Yde GdJYHjQ GdQDjG ef GLd GdYdhe faYkG hGYXegG hbYkG dYehe GdMGLI GdjgG s
(3BNQgG (B:s
(3SYjO Hf SfGf hEjGS Hf eYGhjI hLfOd Hf GdMce heYGhHI Hf cdKhe agPg CSeGDge s
(3GfJNHg ef cJH GdeJbOejfs
(3HQSe NRGfI cJNOG eQGOs
(3cJH Ydi GdUaMI GdChdi Cfg dGHi SYjO GdgQhis
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeI (B- (3U (B132 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3JYHjQ GdQDjGs